2015
DOI: 10.5194/acp-15-10239-2015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tropical cyclones on the tropical tropopause parameters observed using COSMIC GPS RO data

Abstract: Abstract. Tropical cyclones (TCs) are deep convective synoptic-scale systems that play an important role in modifying the thermal structure, tropical tropopause parameters and hence also modify stratosphere-troposphere exchange (STE) processes. In the present study, high vertical resolution and high accuracy measurements from COSMIC Global Positioning System (GPS) radio occultation (RO) measurements are used to investigate and quantify the effect of tropical cyclones that occurred over Bay of Bengal and Arabia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 36 publications
3
21
0
Order By: Relevance
“…These results compare well with higher WVMR observed on the eastern side of cyclones over Atlantic and Pacific oceans (Ray and Rosenlof, 2007). These results also compare well with those reported by Ravindra Babu et al (2015), who used GPS-RO measured relative humidity (RH) and found enhancement in RH on the eastern side of the centre in the upper troposphere (10-15 km) over the north Indian Ocean. Higher WVMR values observed on the eastern side of the cyclone centre might be due to the upper level anticyclonic circulation over the cyclones.…”
Section: Water Vapour Variability In the Utls Region During Cyclonessupporting
confidence: 81%
See 4 more Smart Citations
“…These results compare well with higher WVMR observed on the eastern side of cyclones over Atlantic and Pacific oceans (Ray and Rosenlof, 2007). These results also compare well with those reported by Ravindra Babu et al (2015), who used GPS-RO measured relative humidity (RH) and found enhancement in RH on the eastern side of the centre in the upper troposphere (10-15 km) over the north Indian Ocean. Higher WVMR values observed on the eastern side of the cyclone centre might be due to the upper level anticyclonic circulation over the cyclones.…”
Section: Water Vapour Variability In the Utls Region During Cyclonessupporting
confidence: 81%
“…However, our quantification of the cross-tropopause flux will not be affected by this limitation as earlier studies revealed that the maximum STE occurs during the mature to peak stage of the cyclone. Details on the selection of 16 cyclones are presented in Ravindra Babu et al (2015). In Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations